Preconcentration and Simultaneous Determination of Lead(II) and Copper(II) by N,N''-Disalicylideneethylenediamine by Electro Thermal Atomic Absorption Spectrometry - MOGHIMI, ALI; JAVAD POURSHARIFI, MOHAMAD (Asian Journal of Chemistry, 2010)
A simple, highly sensitive, accurate and selective method for simultaneous determination of trace amounts of Pb(II) and Cu(II) in water samples is presented. The method is based on selective chelation of Pb(II) and Cu(II) on surfactant coated alumina, modified with a Schiff base N,N¢-disalicylideneethylenediamine. The retained ions were then eluted with 4 mL of 4 M nitric acid and determined by electro thermal atomic absorption spectrometry at 283 and 324 nm for Pb and Cu, respectively. The influence of flow rates of sample and eluent solutions, pH, breakthrough volume, effect of foreign ions on chelation and recovery were investigated. 1.5 g of surfactant coated alumina adsorbs 40 mg of the Schiff base which in turn can retain 15.0 ± 0.9 mg of each of both metal ions. The limit of detection (3σ) for Pb(II) and Cu(II) were found to be 5.57 and 1.69 ng L-1, respectively. The enrichment factor for both metal ions are 100. The present method was successfully applied on determination of lead and copper in different water samples. The ions were also speciated by means of three columns system.